#Hashtagging Caste Names: Using Facebook to Track Caste Tags Online. Issue 2 (December 2022) - Raman, P. Anantha; Ratnamala, V.
The caste system enables one group of citizens as dominant another group is oppressed. Tamil Nadu, the so-called Periyar Land, takes pride in dropping caste tags and eliminating caste titles. Verily we have to introspect that we have truly eliminated the caste tags from the public space. India's majority media is heavily dominated by the upper-caste. Social media provided a new platform for ordinary citizens to share their thoughts. Meanwhile, this modern cyberspace and the public sphere enabled by Facebook are free from caste and caste tags. This study will examine how the dominant castes' identities are constructed on Facebook. It will also explore how Facebook enables caste solidarity and caste consolidation rather than caste annihilation. It will investigate the caste discourse of three dominant castes, that is, Nadar, Thevar and Vanniyar on Facebook. Netnography will be employed in this study with participant observation focused on online fieldwork. The study focused on the collection of archival data as it used existing messages, rather than having any researcher interaction with the online community. The posts with hashtags #Nadar, #Thevar and #Vanniyar will be analysed using thematic analysis.